A conceptual study between person-job fit and work environment on work-related quality of life among manufacturing employees - Mohamed Thari, Mohamad Amirul Nizam; Mohd Hassan, Naffisah; Abdullah, Mohd Zulkifli (Universiti Teknologi Mara Selangor, 2025)
Work-related Quality of Life (WRQoL) is considered an important matter for employees in the workplace. Employees with low levels of WRQoL have the potential to be exposed to mental health problems such as stress and worsened depression and burnout. However, employees wanted the task to be suited to their physical and psychological needs in the first place. That is called Person-Job fit or P-J Fit. P-J Fit conceptualisations are “demands-abilities” and “needs-supplies”. Thus, there are studies on the relationship between P-J Fit and WRQoL. Although the employees are suited to the task in the workplace in terms of skill and personality, supporting and threat factors contribute to WRQoL. Such supporting and threat factor in the workplace is the work environment. The work environment can be divided into human body activities and work conditions. The risky work environment will contribute to occupational diseases such as NIHL, WRMSDs, and cancer and occupational accidents. In the context of Malaysia, the manufacturing sectors are the highest contributors to occupational disease and accidents. Thus, this study intends to investigate the relationship between P-J Fit, work environment, and WRQoL among manufacturing employees. The instruments involved in WRQoL, P-J Fit, and the work environment that will be used will be discussed. At the end of this study, a conceptual framework will be formed. The conceptual framework will contribute to the Person-Environment Fit Theory. More factors involving the work environment, such as leadership, culture, and colleague relationships, can be studied in the future. It also can be involved in other sectors according to certain factors or focus on the manufacturing sub-sector.